A case of long-term neurological and respiratory sequelae of inhalational exposure to palytoxin. (30th October 2020) - Chang, Emily; Deeds, Jonathan; Spaeth, Kenneth
Abstract: Palytoxin has been found in several soft coral species which are popular for in-home reef aquariums. Although a limited number of case reports describing acute respiratory distress after inhalational exposure to palytoxin have been reported, there have been no reports regarding the potential long-term effects of inhalational exposure to palytoxin in the literature. This case follows an aquatic specialist in the U.S. over a period of seven years after a single intense occupational exposure to the aerosolized toxin from cleaning of a residential aquarium. Highlights: Occupational exposure to palytoxin from home aquarium maintenance. Inhalational exposure to presumed aerosols generated during the handling of zoanthids. Long-term cognitive and respiratory impairments from one-time exposure to palytoxin.